La satisfacción del cliente y su incidencia en las ventas de la empresa a Gifts del cantón Babahoyo, provincia de Los Ríos, periodo 2023. - Ruiz Bayas, Víctor Hugo (2024)
In a highly competitive global market, customer satisfaction is crucial for loyalty and increased sales, as it directly impacts purchasing choices and the company's image. Within this framework, this study evaluates customer satisfaction and its impact on A Gifts' sales in the Babahoyo canton, in the province of Los Ríos, during 2023. The research uses a qualitative-quantitative method, combining direct observation with the study of information collected through satisfaction questionnaires, customer opinions, and sales results. An exploratory and descriptive approach attempts to understand the connection between customer experience and the company's commercial performance. The findings indicate that most A Gifts customers express impartial satisfaction, which could influence their loyalty and recommendation of the company. In addition, the company relies heavily on word-of-mouth marketing, which restricts its presence. Among the most relevant challenges identified are the optimization of customer service and price perception, crucial elements to consolidate its presence in the market. To boost its competitiveness and ensure sustained development, A Gifts needs to improve its customer service, perfect its digital marketing tactics, and strengthen its presence on the Internet. These will increase customer satisfaction, expand its coverage, and strengthen its growth in the sector.